ENHANCED ENERGY BACKPROPAGATION ALGORITHM - Aal-Yhia, Ahmad (Iraqi Journal of Science, 2024)
The energy backpropagation algorithm (EBP) used the net, which contains twonodes of input layer, hidden layer and output layer. In this paper, we will use a net,which contains three nodes and four nodes of input layer, hidden layer and outputlayer. This study will compares among times of the learning, times of theidentification and times of the converging by using the three nets (2, 3 and 4 nodes)in the Energy back propagation Algorithm. The results of experiments show the netswhich contain three nodes and four nodes have better performance for time of thelearning than the net which contains two nodes, while the net which contains twonodes has better performance for the time of identification and the time ofconverging than the nets which contain three nodes and four nodes.